-6(x+24)=42

Simple and best practice solution for -6(x+24)=42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(x+24)=42 equation:



-6(x+24)=42
We move all terms to the left:
-6(x+24)-(42)=0
We multiply parentheses
-6x-144-42=0
We add all the numbers together, and all the variables
-6x-186=0
We move all terms containing x to the left, all other terms to the right
-6x=186
x=186/-6
x=-31

See similar equations:

| -1/2(x-4)=-8 | | 8+c=-23-25c | | (3x+7)+(3+4x)=180 | | 1/2k=3/k-1/2 | | 5x+20=–5 | | 1/2k=3/k | | 32m+9=86 | | (x^2-3x-28)/(x-1)=x | | 9g-5=3G+37 | | 0.2+2p=75 | | 4x+5x-20+7x-40+6x-40=360 | | −2(x+7)+19=10−3x | | 2.4x+15=2.1x | | x/104=2 | | 1/2(4x-6)=1/2(8x-10) | | 3(2x-2)+10=6(4x+2)+24 | | 0.59x+20=1.09 | | 30-(-6u)=-36 | | 4(2x+1)=4x+6 | | 35^2=b^2+20^2 | | -5x+4+3x=-1-4x-5 | | i+8=42 | | t/3+8=5t/4 | | 2x+21=2(2x+21) | | 3a+10=8a+20 | | i-8=42 | | (2x+10)+48=-80 | | 2x+21=2x+21 | | -5x=240 | | 3^4x=3^3 | | 10+-5x=20 | | 1/2x+14=-40 |

Equations solver categories